2003
DOI: 10.1111/j.1151-2916.2003.tb03435.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Synthesis of a Porous Calcium Zirconate/Spinel Composite with Idiomorphic Spinel Grains

Abstract: Porous CaZrO3/MgAl2O4 composites were synthesized in air by pressureless reactive sintering of an equimolar mixture of dolomite (CaMg(CO3)2), monoclinic zirconia (m‐ZrO2), and α‐alumina powders, with a 0.5 wt% lithium fluoride additive. The reaction behavior of the mixed powders (with/without LiF additive) was studied using high‐temperature X‐ray diffraction. A bulk porous composite resulted from sintering at 1300°C for 2 h (in a nearly closed container, so as to increase the LiF‐doping effect), which consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…In earlier work on hot‐pressed MgAl 2 O 4 spinel, Auger spectroscopy was used to detect the presence of Li several hundred nanometers into the surface of the MgAl 2 O 4 42 . Others have also noted that higher Al/Mg ratios are present near the interfaces of spinel grains sintered in the presence of LiF 37 . Based on these observations the following series () of interactions between MgAl 2 O 4 and LiF above the melting point of LiF is described The formation of a fluorine‐rich melt as shown in would be expected to enhance mass transport; indeed, the large faceted grains observed (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In earlier work on hot‐pressed MgAl 2 O 4 spinel, Auger spectroscopy was used to detect the presence of Li several hundred nanometers into the surface of the MgAl 2 O 4 42 . Others have also noted that higher Al/Mg ratios are present near the interfaces of spinel grains sintered in the presence of LiF 37 . Based on these observations the following series () of interactions between MgAl 2 O 4 and LiF above the melting point of LiF is described The formation of a fluorine‐rich melt as shown in would be expected to enhance mass transport; indeed, the large faceted grains observed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…LiF was not identified in any of the studies, suggesting that it may react with spinel during sintering and/or ultimately was removed from the system. It is known that LiF is active at the interface between spinel grains at higher temperatures 18,19,37 . Furthermore, it has been reported that spinel sintered in the presence of LiF has a substantially higher Al content 17–19,37,38 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarizes the starting materials used in this study. The combination denoted as “DZA” is the same in the previous paper 39 . For the combination of “CZMA,” CaCO 3 and MgO powders were used instead of CaMg(CO 3 ) 2 .…”
Section: Detail Analysis and Latest Findings Of The Cazro3/mgal2o4 Upmentioning
confidence: 99%
“…The Al 2 O 3 /monazite system is expected to be a good porous material because of its favorable properties as described above. The present authors have recently developed uniformly porous CaZrO 3 /MgO and related composites with a three dimensional (3‐D) network structure (UPC‐3D) via a pyrolytic reactive sintering process 13–16 . The pore‐size distribution was very narrow (with pore size of ∼1 μm), and the porosity was controllable (typically ∼30%–50%) by changing the sintering temperature.…”
Section: Introductionmentioning
confidence: 99%